The black stallion revolts - Farley, Walter, 1915-1989.; Eldridge, Harold (New York, Random House, 1953)
When his wild black stallion revolts against the routine and schedule of stable life, becoming a killer and a threat, a plane crash thwarts Alec's plans to give the Black a free run in the desert and brings danger to both boy and horse.
When his wild black stallion revolts against the routine and schedule of stable life, becoming a killer and a threat, a plane crash thwarts Alec's plans to give the Black a free run in the desert and brings danger to both boy and horse.
Keywords: Horses -- Fiction